Different roles of crowdsourcing in the policy cycle: A systematic analysis - TAEIHAGH, Araz (Institutional Knowledge at Singapore Management University, 2016)
Crowdsourcing(Howe in 2006) has evolved and now is loosely applied to situations in which arelatively large group of people are used for their ideas, opinions, expertiseor labour (Lehdonvirta and Bright 2015). Crowdsourcing is now being used in thepolicy making in areas such as transportation (Nash 2009) and urban planning(Seltzer and Mahmoudi 2013). However, Prpić, Taeihagh and Melton (2014c; 2015) havedemonstrated that the use of crowdsourcing in the policy cycle (althoughincreasing) thus far has been limited. Scholars have mainly used opencollaboration platforms in agenda-setting, problem definition and policyevaluation stages and other approaches such as Tournaments or Virtual Labour Marketshave been neglected with a few exceptions. In this paper we focus on theapplication of crowdsourcing as a generic policy tool and systematicallyexamine and categorise the different roles that principal crowdsourcing types cantake in different stages of the policy cycle with special focus on thepotential new roles for crowdsourcing in policy design.